Exposure to non-arsenic pesticides is associated with lymphoma among farmers in Spain. Issue 10 (6th June 2006) - van Balen, E; Font, R; Cavallé, N; Font, L; Garcia-Villanueva, M; Benavente, Y; Brennan, P; de Sanjose, S
Abstract : Objectives: To estimate the risk of lymphoma among farmers in Spain. Methods: This is a multicentre case control study conducted in Spain. Cases were subjects diagnosed with lymphoma according to the World Health Organization (WHO) classification in four hospitals between 1998–2002. Hospital controls were frequency matched to the cases by sex, age, and centre. All subjects were interviewed about jobs ever held in lifetime for at least one year and the exposures in those jobs were recorded. The risk of lymphomas among subjects ever having had a job as a farmer was compared with all other occupations. Farmers were analysed according to the type of farming job performed: crop farming, animal farming, and general farming. Occupational exposure was summarised into 15 main categories: organic dust, radiation, contact with animals, PAH, non-arsenic pesticides (carbamates, organophosphates, chlorinated hydrocarbons, triazines and triazoles, phenoxy herbicides, chlorophenols, dibenzodioxin, and dibenzofuran), arsenic pesticides, contact with meat, contact with children, solvents, asbestos, soldering fumes, organic colourants, polychlorinated biphenyls, ethylene oxide, and hair dyes. Results: Although farmers were not at an increased risk of lymphoma as compared with all other occupations, farmers exposed to non-arsenic pesticides were found to be at increased risk of lymphoma (OR = 1.8, 95% CI 1.1 to 2). This increased risk was observed among farmers working exclusively either as crop farmers or as animal farmers (OR = 2.8, 95% CI 1.3 to 5.8). Risk was highest for exposure to non-arsenic pesticides for over nine years (OR = 2.4, 95% CI 1.2 to 2.8). Conclusions: Long term exposure to non-arsenic pesticides may induce lymphomagenesis among farmers.